2020
DOI: 10.1111/bju.15196
|View full text |Cite
|
Sign up to set email alerts
|

Retzius‐sparing robot‐assisted radical prostatectomy: early learning curve experience in three continents

Abstract: Objective To assess the effect of surgical experience on peri‐operative, functional and oncological outcomes during the first 50 Retzius‐sparing robot‐assisted radical prostatectomy (RsRARP) cases performed by surgeons naïve to this novel approach. Materials and Methods We retrospectively evaluated the initial cases operated by 14 surgeons in 12 different international centres. Pre‐, peri‐ and postoperative features of the first 50 patients operated by each surgeon in all the participating centres were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
(31 reference statements)
1
16
0
Order By: Relevance
“…Conversely, neither BML nor previous BPH surgery may affect the reliability of RS-RARP in terms of PSMs. Noteworthy, we failed to observe a relationship between SE and PSMs, suggesting that the learning process might be longer than expected [30] also in expert hands, as demonstrated in other settings [20]. Nevertheless, the rate of PSMs observed in the current report, is in line with those reported for high-risk PCa patients treated with anterior approach [31,32].…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, neither BML nor previous BPH surgery may affect the reliability of RS-RARP in terms of PSMs. Noteworthy, we failed to observe a relationship between SE and PSMs, suggesting that the learning process might be longer than expected [30] also in expert hands, as demonstrated in other settings [20]. Nevertheless, the rate of PSMs observed in the current report, is in line with those reported for high-risk PCa patients treated with anterior approach [31,32].…”
Section: Discussionsupporting
confidence: 80%
“…To date, some studies have reported the learning curves of LRP and RALRP. An early study reported the safety and efficacy of Retzius-sparing RALRP, and there was a linear relationship between surgery experience and imitated UC in the first 50 cases, without reaching a plateau ( 23 ). Some authors asserted that with >100 cases, the plateau on early continence is achievable ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors asserted that with >100 cases, the plateau on early continence is achievable ( 24 ). Regarding PSMs, the evidence available is controversial: some researchers did not find improvement of the PSM rate during the learning curve ( 23 , 25 ), while others, in a single surgeon series, found an overall reduction of positive margins with the amount of experience ( 26 ). In an early series about traditional RARP, Patel and colleagues ( 27 ) showed that operative times and EBL are reduced with the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative surgical technique avoids damage to the supportive fascial structures of the bladder. In comparison to SA-RARP, the Santorini plexus, the endopelvic fascia, puboprostatic ligaments, and the detrusor apron remain intact in RS-RARP [ 6 ]. Different prospective trials have reported better outcomes in terms of early continence in RS-RARP than SA-RARP, with immediate continence results ranging from 51–76% for RS-RARP compared to 21–60% in SA-RARP [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%